Towards a better understanding of the full impact of the left digit effect on individual trading behaviour: unearthing a trading profit effect. Issue 9 (12th June 2020) - Kansara, Amey Pramodkumar; Sung, Ming-Chien; Ma, Tiejun; Johnson, Johnnie E. V.
ABSTRACT: Investors' perceptions of price have been shown to be disproportionately affected by the left-most digit(s). However, a similar left digit effect (LDE) in relation to another important determinant of investors' behaviour (i.e. trading profit) has not been explored. We examine over 7, 314, 570 trades made by 25, 766 individuals and find a LDE in profit that is 1.71 times stronger than that related to closing price; suggesting that individuals focus more on left digits in profit than price when deciding when to close a trade. In addition, we observe a positive synergistic relationship between the LDE related to profit and price, suggesting that its total influence may result in losses of billions of dollars per financial year for investors. We suggest that these results make a strong case for educating investors against this bias.